Encyclopedia of geobiology - Reitner, J. (Joachim; Thiel, Volker; SpringerLink (Online service (Dordrecht London Springer, 2011)
The interplay between Geology and Biology has shaped the Earth from the early Precambrian, 4 billion years ago. Moving beyond the borders of the classical core disciplines, Geobiology strives to identify cause-and-effect chains and synergisms between the geo- and the biospheres that have been driving evolution of life in modern and ancient environments. Combining modern methods, geobiological information can be extracted not only from visible remains of organisms, but also from organic molecules, rock fabrics, minerals, isotopes and other tracers. Exploring these processes and their signatures also creates enormous applied potentials with respect to issues of environment protection, public health, energy and resource management. The Encyclopedia of Geobiology is designed as a key reference for students, researchers, teachers, and the informed public to provide basic, but comprehensible knowledge on this rapidly expanding discipline at the interface between modern geo- and biosciences
Electronic reproduction.
Keywords: Geobiology -- Encyclopedias; Evolution (Biology); Electronic books